Li9Al4Sn5 as a new ordered superstructure of the Li13Sn5 type. Issue 4 (1st April 2017) - Pavlyuk, Volodymyr; Dmytriv, Grygoriy; Tarasiuk, Ivan; Ehrenberg, Helmut
Abstract : The crystal structure of the trigonal ternary stannide Li9 Al4 Sn5 has been determined by the single‐crystal method. Li9 Al4 Sn5 is a new ordered superstructure of the Li13 Sn5 type and represents the stucture family in which the parent structure belongs to the W‐type. Abstract : Alloys from the ternary Li–Al–Sn system have been investigated with respect to possible applications as negative electrode materials in Li‐ion batteries. This led to the discovery of a new ternary compound, a superstructure of the Li13 Sn5 binary compound. The ternary stannide, Li9 Al4 Sn5 (nonalithium tetraaluminium pentastannide; trigonal, P m 1, hP18 ), crystallizes as a new structure type, which is an ordered variant of the binary Li13 Sn5 structure type. One Li and one Sn site have m . symmetry, and all other atoms occupy sites of 3 m . symmetry. The polyhedra around all types of atoms are rhombic dodecahedra. The electronic structure was calculated by the tight‐binding linear muffin‐tin orbital atomic spheres approximation method. The electron concentration is higher around the Sn and Al atoms, which form an [Al4 Sn5 ] m− polyanion.